The role of exopolymers in the attachment of Sphingomonas paucimobilis - Azeredo, Joana (2000)
The importance of exopolymers in the adhesion of sphingomonas paucimobilis was established by studying the attachment to glass of three mutants with defective gellan production. The attachment assays were performed in either phosphate buffered saline (controls) or in the exopolymeric solutions produced by the mutants. The exopolymer was found to have surface active properties, changing the glass surface from hydrophilic to hydrophobic, making adhesion thermodynamically favourable. Only the cells that had a substantial polymeric layer surrounding their walls were able to significantly colonise glass coated with the exopolymer. It is hypothesised that the exopolymer bound to the glass and the exopolymer present at the surface of the bacteria bound together, overcoming the energy barrier created by the negative charge of both surfaces. It is concluded that the exopolymer from S. paucimobilis has a dual role in the process of adhesion by both coating the surface thereby strengthening adhesion and by enhancing adhesion through the establishment of polymeric bridges.